Hedonic price of housing space - AGARWAL, Sumit (Institutional Knowledge at Singapore Management University, 2021)
This article estimates hedonic prices for different levels of housing space, by exploiting a unique space‐adding project in Singapore that added a uniform amount of space to each existing housing unit regardless of the original size. This space adding program was carried out if sufficient residents vote in favor of space adding. Using a difference‐in‐differences (DiD) strategy after restricting our sample to narrow margins around the voting cutoff, we find that the additional space increased the resale price of a housing unit by 7% on average, and the extent of price appreciation varied significantly across the original size of the units.